Rational Inattention and Migration Decisions - Simone Bertoli; Jesús Fernández-Huertas Moraga; Lucas Guichard (Institute of Labor Economics (IZA), 2020)
Acquiring information about destinations can be costly for migrants. We model information frictions in the rational inattention framework and obtain a closed-form expression for a migration gravity equation that we bring to the data. The model predicts that ows from countries with a higher cost of information or stronger priors are less responsive to variations in economic conditions at destination, as migrants rationally get less information before deciding where to move. The econometric analysis reveals systematic heterogeneity in the pro-cyclical behavior of migration flows across origins that is consistent with the existence of information frictions.
Keywords: F22; D81; D83; 330; rational inattention; information; international migration; gravity equation